A Escolha profissional no ensino técnico do Instituto Federal de Educação Ciência e Tecnologia do Pará-campus Castanhal - SOARES, Mônica Coeli Souza (2018)
The history of professional choice is related to the conception of work in human society, but it has not always occupied a prominent place in man’s life to the point of requiring time and investment for its achievement. The moment of professional choice usually occurs during adolescence; is a decisive moment in the young person's life because, in addition to implying personal fulfillment, it implies social achievement by offering a labor well done to society. Several factors influence the professional choice and are presented with different weight and compositions in the life history of young people. This study had as general objective to investigate the factors that influenced the professional choice for a higher education course of students who has completed the Technical Course in Farming integrated to High School of the Instituto Federal de Educação, Ciência e Tecnologia do Pará – Castanhal Campus. Considering the unique social and historical process of professional choice, the present study is a qualitative research. It was accomplished with 54 students, coming from several municipalities of Pará, at the moment of choosing a higher education course. Participants are male and female, aged between 16 and 24 years old, are covered by the Student Assistance Policy of IFPA Castanhal Campus, and whose families have a per capita income of between 0 and 1 minimum salary. Participants answered a questionnaire, composed of open questions, about the higher education course for which they would take the entrance exam; about the difficulties they encountered in making their choices; reasons and feelings about the choices made; on information received concerning higher education courses offered by IFPA and other higher education institutions in the region; and on the importance of student assistance offered by IFPA-Campus Castanhal. All ethical principles of research with human beings have been preserved. The responses were classified according to the Bardin Content Analysis, categorized in simple frequency and percentage. The analysis of the participants' responses indicated that, in general, the psychological and psychosocial aspects were predominant forces in the professional choice of the participants, that is, considering the 489 units of records of the answers to the questions 1-3-4-5- 6-9 , 70% (f = 320) are psychological and psychosocial. Next, the socioeconomic aspects appear with 27% (f = 131) of percentage of frequency and those of educational order appear with 8% (f = 38). The pretension of entering a higher education not only expressed the questions of satisfaction, identity, personal fulfillment, need to explore the world in which they live, but also revealed the strength of an economic, social and political context acting in the subjective processes of elaboration mental, affectivel and emotional choices for their lives. The students did not consider that the student assistance received to attend the Technical Course in Farming integrated to High School in the IFPA – Castanhal Campus was an influence in the choice of the higher education course.